Study on Toxoplasma Gondii, Leptospira Spp., Coxiella Burnetii, and Echinococcus Granulosus Infection in Veterinarians from Poland - Wójcik-Fatla, Angelina (J Vet Res, 2018)
INTRODUCTION: Exposure to zoonotic factors in veterinary practice is closely related to the nature of the work. The main aim of the study was to determine the risk of selected zoonotic infections among the occupational group of veterinarians in Poland. MATERIAL AND METHODS: Blood samples of 373 veterinarians (162 males and 211 females) from 12 provinces of Poland were collected by the venipuncture of a forearm for serological tests. Commercial immunoenzymatic tests (ELISA) were used for detection of specific IgG antibodies to Echinococcus granulosus, IgM and IgG to Leptospira spp., and IgM, IgA, and I and II phase IgG to Coxiella burnetii. Enzyme-linked fluorescence assays (ELFA) were used to detect IgM and IgG antibodies to Toxoplasma gondii. RESULTS: Positive results were found in 209 (56.0%) veterinarians for at least one of the examined diseases. The overall proportion of participants found to have specific Toxoplasma gondii antibodies in the IgM and/or IgG assays amounted to 44.5%. The presence of Coxiella burnetii antibodies was found in 16 (4.3%) subjects, while Leptospira spp. antibodies were detected in 63 (16.9%) veterinarians. Among the 373 veterinarians examined, no Echinococcus granulosus antibodies were found. CONCLUSION: Results of the study seem to indicate a slightly elevated risk of Toxoplasma gondii infection and a moderate risk of infection with Leptospira spp. and Coxiella burnetii in veterinarians.